Handbook of Food Fortification and Health From Concepts to Public Health Applications Volume 2 - Preedy, Victor R.; Srirajaskanthan, Rajaventhan; Patel, Vinood B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2013)
Handbook of Food Fortification and Health: From Concepts to Public Health Applications Volume 2 represents a multidisciplinary approach to food fortification. This book aims to disseminate important material pertaining to the fortification of foods from strategic initiatives to public health applications. Optimal nutritional intake is an essential component of health and wellbeing. Unfortunately situations arise on a local or national scale when nutrient supply or intake is deemed to be suboptimal. As a consequence, ill health occurs affecting individual organs or causing premature death. In terms of public health, malnutrition due to micronutrient deficiency can be quite profound imposing economic and social burdens on individuals and whole communities. This comprehensive text examines the broad spectrum of food fortification in all its manifestations. Coverage includes sections on definitions of fortifications, fortified foods, beverages and nutrients, fortifications with micronutrients, biofortification, impact on individuals, public health concepts and issues, and selective methods and food chemistry. Handbook of Food Fortification and Health: From Concepts to Public Health Applications Volume 2 is an indispensable text designed for nutritionists, dietitians, clinicians and health related professionals.
Part 1. Novel food vehicles and agents for fortificants -- Chapter 1. Multiple fortified egg for comprehensive nutritional and health support -- Chapter 2. Apple Pomace - Source of Dietary Fibre and Antioxidant for Food Fortification -- Chapter 3. Fortified food made from animal products: From product design to nutritional intervention -- Chapter 4. Dietary lipid sources as a means of changing fatty acid composition in fish: implications for food fortification -- Chapter 5. Meat and meat products enriched with n-3 fatty acids -- Chapter 6. Cheese Fortification -- Chapter 7. Yogurt fortified with date fiber -- Chapter 8. Convenience drinks fortified with n-3 fatty acids: a systematic review -- Chapter 9. Evaporated sugarcane juice as a food fortificant -- Chapter 10. Fortification of Fish Sauce and Soy Sauce -- Part 2. Impact on individuals -- Chapter 11. Targeting pregnant and lactating women and young children with fortified foods -- Chapter 12. Fortification of human milk for preterm infants -- Chapter 13. Fortification of school meals -- Chapter 14. Food fortification and frail elderly nursing home residents -- Chapter 15. Bread as a vehicle vitamin D fortification: application to nursing home residents -- Chapter 16. Learnings from the Postmenopausal Health Study for the effect of dairy products fortified with calcium and vitamin D on bone metabolism -- Chapter 17. Cognition and multiple micronutrient fortification of salt -- Part 3. Public health, concepts and issues -- Chapter 18. Food fortification as a global public health intervention: Strategies to deal with barriers to adoption, application and impact assessment -- Chapter 19. Why food fortification with vitamin B12 is needed -- Chapter 20. Folic acid to prevent neural tube defects: success and controversies -- Chapter 21. Vitamin D Fortification in North America: Current Status and Future Considerations -- Chapter 22. Profiling national mandatory folic acid fortification policy around the world -- Chapter 23. In-home fortification of complementary feedings: Chinese perspectives -- Chapter 24. Food fortification: a regulator$1 (Bs perspective -- Part 4. International perspectives -- Chapter 25. Fortification of flour and outcomes: Oman$1 (Bs perspective - contextual considerations and outcome -- Chapter 26 - Strategies to improve micronutrient status of infants and young children with special attention to complementary foods fortified with micronutrients: Perspectives from Viet Nam -- Chapter 27. Food Fortification Programs in Pakistan -- Chapter 28. Neural tube defects in Australia and food fortification with folic acid -- Chapter 29. Vitamin D supplementation in children: Indian perspectives -- Chapter 30. Use of fortified foods for Indonesian infants -- Chapter 31. Micronutrient fortification of school lunch meals in Himalayan villages -- Chapter 32. Iron Fortification Strategies in Brazil -- Chapter 33. Iron-Fortified and Unfortified Nigerian Foods -- Chapter 34. Food fortification: What more is there to know?.s
Keywords: Medicine; Food science; Nutrition; Public health; Internal medicine; Personal health and hygiene; Medicine & Public Health; Clinical Nutrition; Nutrition; Food Science; Internal Medicine; Public Health; Health Promotion and Disease Prevention